Probing E-cadherin Targeting Peptides Using Atomic Force Microscopy - Studd, Adam (2022)
A significant current research effort is focussed on a need to understand and regulate embryonic stem cell function in vitro, as their potentially limitless self-renewal and differentiative capacity could provide an effective approach for countless applications, including the development of therapeutics. As such, discovery of targeting peptides to influence stem cell behaviour, or isolate and understand cell mechanisms, is an ideal method to improve current understanding. E-cadherin is a cell surface adhesion protein commonly expressed by mESCs, and is highlighted as a potential target to probe and manipulate cell functions for a wide range of biological applications, such as preventing cell differentiation in large scale bioreactors. Due to the biological and mechanical influence of E-cadherin on cell functions, such as maintenance of pluripotency and formation of cell-cell contacts, there is ongoing research into the development of E-cadherin targeting peptide sequences to uniquely influence mESC characteristics. One recent example is the development of the Epep (SWELYYPLRANL) sequence, and subsequent analogue EpepW2R (SRELYYPLRANL), that were shown to uniquely affect cell expression of key transcripts while inhibiting and not inhibiting cell-cell contacts, respectively. However, the relationship between the physical and biological effects actioned by these peptides requires further research to understand the processes involved. Atomic force microscopy (AFM) is a diverse and widely available technique often employed for the analysis of binding proteins, such as E-cadherin. Previous studies demonstrate the ability to use single molecule force spectroscopy (SMFS) to isolate individual protein adhesions, providing unique insight into the bond mechanics when compared to commonly used ensemble analysis such as surface plasmon resonance (SPR). However, the potential for AFM to be used as a complimentary technique to aid in the development and analysis of novel peptides has not yet been explored. Therefore, the work in this thesis aimed to use a multidisciplinary approach to explore the potential of a unique method for peptide screening using AFM, by probing the influence of Epep and EpepW2R targeting peptides on single molecule E cadherin adhesions, while conducting complimentary cellular-based assays to probe the peptide mediated response of mESCs. In this thesis we developed an SMFS AFM system capable of isolating single molecule E-cadherin adhesions between samples and AFM probes functionalised with the extracellular domain of E-cadherin. This system was subsequently used to probe the mechanical response of these samples in the presence of Epep and EpepW2R peptides, providing unique insight into their physical inhibitory effect. In contrast to previous literature, we observed that both peptide sequences were capable of a reversible inhibition of E-cadherin adhesions, with preliminary experiments on mESC monolayers highlighting the potential to develop this approach in future work. Complementary biological assays, such as high-content Operetta imaging, presented a unique response of E14 and Ecad-/- mES cell lines in the expression of key targets, including surface proteins and pluripotency markers, following the addition of Epep and EpepW2R. In summary, this work explored the biophysical impact of E-cadherin targeting peptides, using AFM to observe sensitive responses not previously seen in literature, and investigating potential off-target interactions, thus highlighting the potential for this approach to be used in future peptide screening experiments.